2016
DOI: 10.1002/hfm.20667
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Job Rotation Types on Productivity, Accident Rate, and Satisfaction in the Automotive Assembly Line Workers

Abstract: This study investigates different autonomous job rotation types to analyze their impacts on productivity, accident rate, and worker's satisfaction. The subjects of research were 422 assembly‐line units in 3 production plants from an automobile company. The preferred rotation types and workers’ satisfaction scores in the 422 units were surveyed by the average worker's experience and work productivity, quality and accident rate scores were traced over a 5‐year period. Results showed that workers with little work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Developing a job rotation plan is a complex problem. The type of job rotation implemented affects the results in terms of satisfaction and productivity [23,24], and there are a lot of criteria and restrictions that must be considered simultaneously to obtain an efficient solution. For example, it is necessary to find the sequence of tasks that maximizes the variation in the muscle groups being utilized by the workers [25,26] and the optimal length of the rotation interval to reduce monotony and boredom.…”
Section: Introductionmentioning
confidence: 99%
“…Developing a job rotation plan is a complex problem. The type of job rotation implemented affects the results in terms of satisfaction and productivity [23,24], and there are a lot of criteria and restrictions that must be considered simultaneously to obtain an efficient solution. For example, it is necessary to find the sequence of tasks that maximizes the variation in the muscle groups being utilized by the workers [25,26] and the optimal length of the rotation interval to reduce monotony and boredom.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the extant literature generally discuss the job rotation approach as a way of reducing musculoskeletal diseases (Frazer et al, 2003; Jeon & Jeong, 2016; Sana et al, 2019). In this context, it can be said that an employee's excessive exposure to HAV, such as constantly operating the same body part, is likely to produce the results that must be considered as an occupational disease.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Training intervention results showed that the stress response of the experimental group was significantly reduced after the stress management intervention, indicating the effectiveness of the intervention which was similar to previous results in other occupational fields. The group psychological counseling of pressure management is a common project of the employee assistance program through several stages of group activities, from guiding the employees to understand the generation and performance of pressure to master the skill of pressure management, so that trainees can fully master the psychological skills of self-decompression [3] . In addition, in this study, in order to take into account the high stress response of some employees, it was impossible to use group psychological support for all of them.…”
Section: Suitable Stress Management Interventionmentioning
confidence: 99%
“…that cannot be ignored in the human resource management of vehicle enterprises [1][2] . Some studies have found in many occupational fields that, through a series of stress-reducing intervention measures such as pressure management group counseling and individual psychological counseling, the job satisfaction of miners, customer service employees and other professional groups can be effectively improved [3][4][5] . However, there is no research on the stress management intervention to understand its response to the pressure of employees in the auto industry impact of job satisfaction.…”
mentioning
confidence: 99%